Alcohol Consumption and the Impact of Lockdowns - A Study in Thailand - Tantiwat, Waranan; Yang, Wei (Journal of Applied Economics and Management Strategy, 2024)
The COVID-19 pandemic unveiled widespread alcohol consumption as a global coping mechanism for individuals facing fear, loneliness, and stress. The primary research goal is to address the gap concerning the link between COVID-19 lockdowns and alcohol consumption in Thailand. By employing a regression model rooted in economic demand theory which incorporates demographic variables, COVID-19 impacts, and seasonal variations, and utilizes data spanning 40 quarters from 2013 Q1 to 2022 Q4, key variables such as GDP, price, and population are found to significantly influence alcohol consumption. Notably, the study identifies a shift in alcohol from being an inferior to a normal good during the pandemic. This study shed light on the lasting consequences of lockdown-induced alcohol consumption on public health and support strategies for vulnerable populations. The findings contribute to a more comprehensive understanding of the enduring impact of lockdowns in Thailand and their association with the use of alcohol as a coping mechanism. These findings lay the groundwork for addressing public health challenges and designing targeted policy interventions to mitigate the long-term effects of increased alcohol consumption during lockdowns.